Interchangeability, immunogenicity and safety of a combined 10-valent pneumococcal Haemophilus influenzae protein D conjugate vaccine (Synflorix) and 13-valent-PCV (Prevenar13) schedule at 1-2-4-6 months: PREVIX_COMBO, a 3-arm randomised controlled trial. (April 2021) - Leach, Amanda Jane; Mulholland, Edward Kim; Santosham, Mathuram; Torzillo, Paul John; McIntyre, Peter; Smith-Vaughan, Heidi; Wilson, Nicole; Arrowsmith, Beth; Beissbarth, Jemima; Chatfield, Mark D.; Oguoma, Victor M.; Licciardi, Paul; et al.
Highlights: A mix of Synflorix TM (S) and Prevenar13 TM (P) at 1 –2-4–6 months (S SSP) is safe. At 7 months the S SSP schedule is immunogenic against 13 serotypes* and protein D. One-month dose of Synflorix is immunogenic* (8 of 10 serotypes) Two-month dose of Prevenar13 is poorly immunogenic** (8 of 13 serotypes) Two-month dose of Synflorix is superior (8 serotypes) or similar (4) to Prevenar13 *GMC ≥ 0·35 µg/mL **GMC ≤ 0·35 µg/mL. A 4-dose schedule is superior to either 3-dose schedule, particularly against 6B, 19F, and 23F. Abstract: Background: Aboriginal children living in remote communities are at high risk of early and persistent otitis media. Streptococcus pneumoniae and non-typeable Haemophilus influenzae (NTHi) are primary pathogens. Vaccines with potential to prevent early OM have not been evaluated in this population. We compared immunogenicity (ELISA and opsonophagocytic activity) of a combination of Synflorix™ (PHiD-CV10, 10 serotypes and protein D of NTHi) and Prevenar13™ (PCV13, 10 serotypes plus 3, 6A, and 19A), with recommended schedules. Methods: This open-label superiority trial randomised (1:1:1) Aboriginal infants at 28 to 38 days of age, to PCV13 (P) at 2–4-6 months (_PPP), PHiD-CV10 (S) at 2–4-6 months (_SSS), or PHiD-CV10 at 1–2–4 plus PCV13 at −6 months (S SSP). Primary outcomes (blinded) were immunogenicity against PCV13-only serotypes 3, 6A, 19A, and PHiD-CV10-only protein D at 7 months. Secondary outcomes include immunogenicity against all serotypes at 2, 4 and 7 months. Findings: Between 2011 and 2017, 425 infants were allocated to _PPP(143), _SSS(141) or S SSP(1 4 1). An intention to treat approach including all available data was used. The S SSP group had superior immunogenicity against serotypes 3, 6A, and 19A compared to _SSS (OPA GMT ratios 8.1 to 59.5, p < 0.001), and against protein D compared to _PPP (GMC ratio 11.9 (95%CI 9.7 to 14.6)). Immune responses to protein D and 3, 6A, and 19A in S SSP were not significantly lower (i.e. no harm) than either _SSS or _PPP. For ten common serotypes responses at 2, 4 and 7 months were superior for S SSP (following 1-, 2-, and 4- doses) than _SSS and _PPP (following 0-, 1-, and 3- doses). At 4 months, _SSS was superior to _PPP. Reactogenicity and hospitalisations were rare and unrelated to the intervention. Interpretation: From two months, the 1–2–4–6-month combined schedule (S SSP) was safe and significantly more immunogenic than 2–4–6-month schedules. The earlier responses may be beneficial in high-risk populations.